1998
DOI: 10.1007/s004140050196
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of selectins in human skin wounds

Abstract: The aim of the study was to characterize the vitality and age of skin wounds by the detection of selectins. A prospective study was conducted for this purpose in which 197 vital human skin wounds (time since injury ranging from 3 min to 790 days) were investigated immunohistologically. Of the samples tested, 97 were taken from autopsy material and 100 from patient material from the department of surgery at the university hospital. The selectins were detected in paraffin sections after autoclaving and using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Wound age determination is closely involved in the pathophysiology of the wound healing process. With advances in biochemical and immunohistochemical techniques, several markers have been applied to wound age determination [3,4,5,6,7,8] and immunohistochemical analysis is now exclusively utilized for wound age determination [9,10,11,12,13,14,15,16,17,18,19,20,21]. VEGF has been characterized as an angiogenic growth factor from media conditioned by bovine pituitary folliculostellate cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound age determination is closely involved in the pathophysiology of the wound healing process. With advances in biochemical and immunohistochemical techniques, several markers have been applied to wound age determination [3,4,5,6,7,8] and immunohistochemical analysis is now exclusively utilized for wound age determination [9,10,11,12,13,14,15,16,17,18,19,20,21]. VEGF has been characterized as an angiogenic growth factor from media conditioned by bovine pituitary folliculostellate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many studies on forensic wound age determination have been performed [3,4,5,6,7,8,9,10]. Recently, biological substances such as growth factors, cytokines, and adhesion molecules have become useful markers for wound age determination [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In forensic practice, it is most important to determine the post-infliction intervals of skin wounds or brain injuries, because forensic pathologists are required to judge how wounds or injuries are related to the cause of death [3][4][5][6][7][8][9][10][11][12]. Similarly, in cases of pulmonary thromboembolism, forensic pathologists have to determine the age of a thrombus in order to judge the causal relationship between the venous thrombus and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…As the percentages of polymorphonuclear neutrophils, mononuclear cells, and fibroblastic cells in injured zones reportedly change over time [18,[20][21][22], they may have potential use in estimating wound age. Some studies have reported a positive correlation between an early wound stage and markers' levelseven as early as 1998 when Dressler et al [23] observed strongly positive immunohistochemical reactions for P-selectin 3 min after wound creation. The above findings will be useful in future studies.…”
Section: Morphological Analysismentioning
confidence: 99%